COMPARISON OF UV-VIS SPECTROPHOTOMETRY, POTENTIOMETRIC TITRATION, AND CONDUCTOMETRY METHODS IN THE DETERMINATION OF VITAMIN C CONTENT IN COMMERCIAL BEVERAGES - Haidhar Arvin Hidayatullah; Ahmad Wahyu Aprillianto; Arka Raditya Akmal; Faramufida Fricha Fricha; Venus Ramadhani Farichah; Meisela Rosalina Dewi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Verification of vitamin C content in commercial packaged beverages is an important analytical need, given the chemical instability of ascorbic acid under various environmental factors that can cause the actual content to deviate from the declared label value. This study aimed to compare the analytical performance of three vitamin C determination methods, namely UV-Vis spectrophotometry, potentiometric titration, and conductometry, applied to a commercial beverage sample claiming 1000 mg vitamin C per 500 mL. UV-Vis spectrophotometric analysis was performed by constructing a five-point calibration curve at 265 nm, potentiometric titration was conducted using 0.1000 N NaOH with continuous pH-based equivalence point detection via a calibrated glass electrode, and conductometry was performed by monitoring changes in electrical conductivity during neutralization with volume correction applied at each point. Each method was performed in five replicates. The results showed that UV-Vis spectrophotometry provided the best performance with a mean measured content of 1024.0 mg/500 mL, %error of 2.48%, and %RSD of 0.85%. Potentiometric titration yielded a mean content of 1038.7 mg/500 mL with %error of 3.87% and %RSD of 1.65%. Conductometry produced the largest deviation with a mean content of 1072.3 mg/500 mL, %error of 7.23%, and %RSD of 4.22%. The high deviation in conductometry was attributed to matrix interference from various ions and organic acids in the beverage contributing to the total conductivity response, while variability in potentiometric titration was influenced by the sensitivity of equivalence point detection to titrant addition rate and the non-selective response to all titratable acids in the sample. UV-Vis spectrophotometry is recommended as the most reliable and practical method for determining vitamin C content in complex commercial beverage matrices under routine analytical laboratory conditions.